The Influence of Pictorial Card Media on Early Childhood Reading Literacy Abilities - Mu'awanah Mu'awanah; Ajat Ajat (Journal of Childhood Development, 2024)
Picture Card Media is not only a learning tool, but also an effective strategy in improving early childhood reading literacy. This study aims to identify the effect of using picture card media on reading literacy skills in group B children at RA Jami`atul Jannah, Sungai Pelunggut Village, Sagulung Sub-district, Batam City. Reading literacy is defined as a language skill that involves reading, writing, listening, speaking and thinking, within the context of social, historical and cultural practices. The study sample included 28 children in group B, with a quantitative approach and descriptive method. Primary data was collected, and simple linear regression analysis showed that the use of picture card media had a significant effect on children's reading literacy, with a coefficient value of 1.358. The results show that picture card media is effective in improving children's early reading literacy skills, providing a significant role and influence in the development of early reading skills